Salmonella Bacteremia in Hospitalized Ugandan Children with Febrile Illness - Appiah, Grace D.; Mpimbaza, Arthur; Kigozi, Ruth; Sserwanga, Asadu; Kapisi, James; Kamya, Moses R.; Nanteza, Jane Frances; Kajumbula, Henry M. (AMER SOC TROP MED & HYGIENE, 2017)
Salmonella is a known cause of acute febrile illness (AFI) among children in sub-Saharan Africa; however its contribution to bacterial blood stream infections is poorly defined due to limited diagnostic capacity. To address this gap and to inform accurate patient diagnosis and treatment, improved AFI surveillance and expanded diagnostic testing is needed.
Keywords: Febrile Illness; Salmonella Bacteremia; Children